Integrasi Al-Qur’an dalam Tata Kelola Perusahaan: Mewujudkan Good Corporate Governance Melalui Harmonisasi Spiritual - Hirman, Akhmad Akram; Hamidah, Hamidah; Rahman, Zakiyyah Iftinaan; Taskurun, Taskurun (Jurnal Ilmiah Ekonomi Islam, 2024)
Good Corporate Governance (GCG) is the principal companies apply to maximize corporate value, improve performance, and ensure transparency and accountability in the company's management. Therefore, this research applies two perspectives related to GCG principles and the Qur'anic perspective, focusing on the deeper relationship between GCG principles and the teachings of the Qur'an. In collecting data, this research uses interview instruments derived from these employees through a case study research approach to integrate the Qur'an in GCG practices in companies engaged in food and beverage in Makassar City. In addition, the results of this study are implementing the principles of Good Corporate Governance (GCG) in the company by considering the integration of the Qur'anic verses by applicable regulations. Nevertheless, there is a need to increase transparency and accountability, especially in providing salaries according to the mutually agreed work contract.